On-Screen Prototypes: Making Speculative Designs For And Through Animation - Nielsen, Trygve (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
This paper gives a short insight into the author’s exhibition and book project Visual Music Design Fiction, a project that explores both adventurous and silly interconnections between sound and animation and simultaneously addresses problems within contemporary media technology. The text positions the project in relation to speculative design and design fiction, traditions that encompass design proposals that are made to critically explore technological or societal developments rather than to make commercially viable products. Further it draws lines between these and wider artist/inventor traditions. Based on experiences from the project it is being demonstrated how the craft of animation can be applied to model processes, and such work as an “expanded draughtsmanship” for the artist/inventor.